(untitled) (Journal of history, 2023)
With the formation of the Republic of Turkey and M.K. Ataturk’s accession to government, the ideological policy of the state was based on the principles of unifying the peoples under the single nation. This required the implementation of a language and nationality policy. The preparation and transition to the Latin alphabet was followed by a policy of “cleaning” the Turkish language from Arabo-Persian elements. A combination of national policies were the main points in the implementation of the “Turkish nation” mentality. Every citizen, irrespective of his/her nationality, started to be referred to as a Turk by official documents in the newly established state in 1923. M.K. Ataturk’s policy of national identity eventually led to the consolidation of the peoples of all of Turkey. The implementation of this policy entailed both the use of harsh methods and the fight against the scholastic religious leaders and the forcible introduction of a new alphabet. These innovations and the abrupt rejection of the Arabic alphabet naturally aroused the discontent of some sections of the population. Considering the totality and the aims of M.K.Ataturk’s policy, the process of nation building as reflected in modern Turkey must be emphasised. Today, despite the ideologisation of society as a whole and its division into several branches of right-wing and left-wing, the population of Turkey has a strong sense of national cohesion due to threats to national security from the outside. The current domestic and foreign policy of R.T. Erdogan in the Middle East and the Black Sea region is proof of this. Naturally, these historical processes increase the relevance and necessity of the study. In this study historical continuity, content analysis, historicism, comparative analysis of politics and national identity process and critical approach to language policy have been used. Keywords: Turkey, M.K. Ataturk, language policy, national identity